Canva Based Learning Media: Students Learning Outcomes In Senior High School - Nurul Alamia; Rahmi; Sitti Maryam Hamid (Journal of Conflict and Social Class (JCSC), 2024)
Students' understanding in learning English, especially in advertising texts, is still low. They have difficulty understanding and processing the information in advertising texts using only limited learning media. Therefore, a solution is needed to optimize the effectiveness of advertising text learning. By using the Canva application you can overcome this problem. The aim of this research is to help teachers and students explore and make it easier to learn advertising text material, helping students understand advertising text through visual representations created with the Canva application. The subjects of this research were class X students. This research used a qualitative descriptive method with data collection techniques through observation, interviews and questionnaires, as well as data reduction data analysis techniques. The results of this research show that the use of the Canva application media in learning English advertising texts was considered effective and interesting by 100% of the students who were research subjects. Students easily understand advertising learning text material after using Canva and increase student involvement in the learning process.